Mandate of State Authorities, Connected Laws and Guidelines of the National Human Rights Commission in Addressing the Menace of Bonded Labour in India - Om Prakash Vyas, Aneesha PR (Journal of Informatics Education and Research, 2025)
Bonded labour continues to be a critical human rights issue in contemporary India. Despite passing of the historic social welfare legislation[1], the Bonded Labour System (Abolition) Act 1976, the government is still struggling and combating with this social menace[2]. This research paper provides a comprehensive overview of the laws of land, the policies in place in the light of causes, prevalence, and consequences of this social problem within the Indian context. Emphasis has been given on the specific laws related to identification, rescue, release and rehabilitation of bonded labourers[3]. The measures currently being taken by the State and rights bodies such as, the National Human Rights Commission (NHRC) to address the issue of bonded labour are also explored[4]. The paper offers a detailed analysis of the factors contributing to the perpetuation of bonded labour in India, including poverty, lack of education, caste-based discrimination, and insufficient enforcement of labour laws. Furthermore, this paper delves into the actions of various stakeholders, especially state bodies, which combat bonded labour. There is no dearth of laws but the problem lies in its implementation[5]. The Apex Court of India has given a vast mandate[6] to the National Human Rights Commission but the task still remains uncompleted. The State often remains in a denial mode on the very existence of bondage[7]. If at all, identification, rescue and release of bonded labourers does take place, they are seldom rehabilitated[8] despite the establishment of a robust rehabilitation scheme by the central government[9] . There is still a lack of awareness on the laws of land amongst the stakeholders and sadly, conviction of the errant employers under the Summary Trial remains mostly unheard[10]. This paper also provides some recommendations for breaking the cycle of exploitation and empowering victims to regain their autonomy and self-respect.